Comparative analyses of nuclear proteome: extending its function - Narula, Kanika; Chakraborty, Niranjan; Datta, Asis; Chakraborty, Subhra (Frontiers in Plant Science, 2013)
Organeller proteomics is an emerging technology that is critical in determining the cellular signal transduction pathways. Nucleus, the regulatory hub of the eukaryotic cell is a dynamic system and a repository of various macromolecules that serve as modulators of such signaling that dictate cell fate decisions. Nuclear proteins are predicted to comprise about 10-20% of the total cellular proteins, suggesting the involvement of the nucleus in a number of diverse functions. Indeed, nuclear proteins constitute a highly organized but complex network that plays diverse roles during development and physiological processes. In plants, relatively little is known about the nature of the molecular components and mechanisms involved in coordinating nuclear protein synthesis, their action and function. Proteomic study hold promise to understand the molecular basis of nuclear function using an unbiased comparative and differential approach. We identified a few hundred proteins that include classical and non-canonical nuclear components presumably associated with variety of cellular functions impinge on the complexity of nuclear proteome. Here, we review the nuclear proteome based on our own findings, available literature, and databases focusing on detailed comparative analysis of nuclear proteins and their functions in order to understand how plant nucleus works. The review also shed light on the current status of plant nuclear proteome and discusses the future prospect.